2022
DOI: 10.1016/j.matpr.2021.11.512
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction with capsule network for the COVID-19 disease prediction though X-ray images

Abstract: Past couple of years, the world is going through one of the biggest pandemic named COVID-19. In the mid of year 2019, it is a very difficult process to predict the COVID-19 just by viewing the images. Later on AI based technology has done a significant role in the prediction of COVID-19 through biomedical images such as CT scan, X ray etc. This study also implemented the deep learning model for the prediction of COVID-19 through X-ray images. The implemented model is termed as XR-CAPS which consist of two mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Darji et al demonstrated a prediction model for COVID-19 based on chest X-ray images. This model consisted of two sub-models that called the U-Net and the capsule network [ 25 ]. Li et al introduced a model to select the “k” value and determined the penalty factor “α” values.…”
Section: Related Workmentioning
confidence: 99%
“…Darji et al demonstrated a prediction model for COVID-19 based on chest X-ray images. This model consisted of two sub-models that called the U-Net and the capsule network [ 25 ]. Li et al introduced a model to select the “k” value and determined the penalty factor “α” values.…”
Section: Related Workmentioning
confidence: 99%
“…The dataset however was smaller with 50 normal and 50 COVID-19 patients. This study [ 57 ] developed a deep learning model called XR-CAPS that incorporates a UNet model for image segmentation and a capsule network for feature extraction for the prediction of COVID-19 from CXR images. The dataset consisted of 896 patients who were either healthy, had pneumonia or were COVID-19 positive.…”
Section: Covid-19 Prediction Using Deep Learningmentioning
confidence: 99%
“…DL was used alongside thoracic CT images to create a complete AI system that detects COVID-19 and measures severity and disease progression [ 77 ]. A DL model (XR-CAPS) was created by Darji et al [ 78 ] to segment and extract points in CXR images to predict COVID-19. The model fuses a UNet model and capsule network for segmentation and feature extraction, respectively.…”
Section: Ai For Covid-19 Diagnosismentioning
confidence: 99%
“…After running the model, the study achieved accuracy, sensitivity, and specificity scores of 93.2%, 94%, and 97.1%, respectively. López et al [ 79 ] used a similar method as Darji et al [ 78 ], achieving an 86.30% accuracy score after attempting to differentiate between COVID-19 and other non-pneumonia cases.…”
Section: Ai For Covid-19 Diagnosismentioning
confidence: 99%